Sekolah penggerak program: a comparative case study in Indonesia’s elementary school context - Fatimah, Halida; Fitriani, Somariah; Priyono, Dwi (Intelektual Pustaka Media Utama, 2024)
The main reason for the research significance is misconceptions arising in the field when implementing Sekolah Penggerak Program, which started in 2021. Thus, the objectives of this study are to describe programs for enhancing exceptional human resources, and to explore the Kurikulum Operasional Satuan Pendidikan (education unit operational curriculum), and the Merdeka Curriculum learning. Four elementary schools in Indonesia's urban and rural areas served as the research unit for analysis, which used a qualitative comparative case study design. The results demonstrate that the programs of ministry of education, culture, and technology research for improving human resources, which includes training and mentoring, have a favourable effect on both rural and urban primary schools. However, only one out of four schools examined the context of the educational unit while creating education unit operational curriculum documents, and every school simply used education unit operational curriculum as a prerequisite for administrative fulfilment. Based on the available components, all teachers developed teaching modules for the Merdeka Curriculum. It was found, nevertheless, that the students were not genuinely exposed to the content of these modules.